Perceptions and knowledge of diabetes in poor urban communities in Accra, Ghana - Raphael Baffour Awuah; Publa Antwi; Olutobi Adekunle Sanuade; Sandra Boatemaa Kushitor; Akanksha Abhay Marphatia; Irene Akwo Kretchy; Samuel Amon; Ann Blandford; Megan Vaughan; Leonard Baatiema; Edward Fottrell; Hannah Maria Jennings (Global Public Health)
Diabetes is a major public health concern, leading to costly and life-threating complications while significantly impacting quality of life. However, limited evidence exists on how diabetes is understood in poor urban communities in Africa, including Ghana. Evidence suggests that community beliefs about disease can shape health outcomes and influence intervention strategies. This cross-sectional qualitative study assessed perceptions and knowledge of diabetes in two poor urban communities in Accra, Ghana. Thirteen focus group discussions were conducted, involving ninety-four participants segmented by sex, age, and diabetes status. Participants frequently cited unhealthy diets, alcohol consumption, and smoking as primary causes of diabetes. Knowledge of prevention was primarily focused on maintaining a healthy diet and engaging in physical activity. Managing diabetes was associated with adopting healthy lifestyles and seeking care at a health facility. Additionally, covert diabetes-related stigma was observed in the communities, with implications for illness disclosure and overall quality of life. Community-wide interventions are needed to increase awareness on the causes and consequences of diabetes, address negative social norms, and expand screening programmes to facilitate early detection and guidance for effective disease management.